Relapse Prevention: An Introduction to Marlatt's Cognitive - Behavior Model - Farshad Nemati (Drug Control Headquarters, Research and Education Office, 2002)
High rate of relapse after apparently successful treatment is a common problem facing with most approaches to treatment of drug dependency. This has led to the development of a variety of strategies for relapse prevention. Among these, Marlatt's cognitive - behavioural model has received a good deal of attention. It is based on two major axes: Identification of warning sings and development of necessary skills for coping with risk situations. In fact, client's perception relating to their abilities to cope with high - risk situations can lead to lapse. Relapes is a function of client's reaction to this initial lapes.Since formal training for addiction counsellors typically includes instruction on Marlatt's relapes taxonomy and intervention strategies have been designed based on his classification systems of high - risk stimuli, it is nececsary for addiction counsellors to become familiar with this system. This paper presents an overview of Marlatts taxonomy of high - risk situations for relapse and his approach to relapse prevention. Special attention is given to definition of relapse, stages of relaps and relapse prevention strategies.